Business resilience : a practical guide to sustained progress delivered at pace /: a practical guide to sustained progress delivered at pace. (2022) - Roberts, David; Choudhury, Islam; Kovela, Serhiy; Roberts, Sheila; Tanvir, Jawwad
No abstract available